Expanded cardboard waste sorting and occupational exposure to microbial species. (15th March 2019) - Madsen, Anne Mette; Frederiksen, Margit W.; Mahmoud Kurdi, Iman; Sommer, Sussi; Flensmark, Elisabeth; Tendal, Kira
Graphical abstract: Highlights: Exposure during collection of an expanded cardboard waste fraction (ECF) is studied. Fungal exposure during collection of ECF increases with reduced collection frequency. Collection of ECF caused exposures to food-related microorganisms and pathogens. ECF is associated with exposure to species normally related to residual waste. Introduction of new waste fractions is associated with reduced collection frequencies. Abstract: Member states of the European Union have to maximize recycling. The current, Danish cardboard recycling system can be improved by increasing the kinds of cardboard products that can be recycled to include e.g. used beverage cartons and pizza boxes (i.e. an expanded cardboard fraction (ECF)). This study aims to obtain knowledge about exposure to airborne endotoxin and microorganisms at species level at different collection frequencies of ECF, and whether an increase in waste sorted fractions means that each waste fraction is collected less frequently. Bacterial and endotoxin concentrations were associated significantly with temperature inside the waste containers and endotoxin and fungal exposures with collection frequency. The concentration of fungi was highest at the truck back and for reduced collection frequencies. The geometric mean diameters of particles with bacteria were between 3.0 and 5.2 μm and with fungi between 3.8 μm and 6.0 μm. In total, 81 and 25 different bacterial and fungal species were found at the waste receiving plant, respectively. Work with ECF caused exposures to food-related microorganisms (e.g. Arthrobacter arilaitensis and Penicillium camemberti ), potential pathogens (e.g. Bacillus cereus, Salmonella sp. and P. expansum ), and commensal bacteria. Bacillus cereus and Salmonella were found in the particle size fraction often being swallowed. Workers collecting EFC will be at risk of being exposed to microbial species that normally are related to residual waste. It seems to be advisable with an EFC collection frequency shorter than eight weeks. However, introduction of new waste fractions has generally been associated with reduced collection frequencies.